Stability Study of Bhallataka Kshaudra: An Ayurvedic Formulation (Asian Journal of Pharmaceutics (AJP), 2019)
Introduction: Bhallataka (Semecarpus anacardium L.), commonly known as â€œmarking nut,â€ has vast applicability in indigenous system of medicine and is indicated in many ailments such as skin disorders, tumors and malignant growth, fungal disease, excessive menstruation, vaginal discharge, fever, hemoptysis, constipation, and intestinal parasites. About 40 formulations of Bhallataka are mentioned in Bharat Bhaishajya Ratnakar. Acharya Charaka has described ten different formulations of Bhallataka in Rasayana Adhyaya. Bhallataka Kshaudra is among the 10 Kalpana of Bhallataka. The ratio of Kshaudra (Honey):Bhallataka oil: Ghrita (Ghee) is 1:8:16, respectively, for the preparation of Bhallataka Kshaudra. Objectives: The stability study is carried out to establish the duration of shelf life of the product under specified storage condition. Materials and Methods: Accelerated stability study was carried out under atmospheric condition temperature: 40 Â± 2Â°C and relative humidity: 75 Â± 5%. Organoleptic parameters, physicochemical parameters, microbial limits, and heavy-metal analysis were observed studied during the study. Results: No significant change was observed in any of the parameters observed during the stability study. Based on the stability data, the shelf life expected to be 4.49 years. Conclusion: The extrapolated shelf life of Bhallataka Kshaudra is found to be 4.49 years on assessing the analytical parameters. The microbial count and heavy metals were within permissible limits.